The influence of extended warranty policy in Malaysian culture perspective : a case study in automobile - Osman Widaa, Amro (2008)
The term of extended warranty has recently appeared in Malaysia industrial market, although it has appeared in the developing countries for quite since the passage of the Magnuson-Moss Warranty—Federal Trade Commission Improvement Act in 1975. Since that era, researchers and scholars has been extensively studied it. In this paper our goal is to study the Malaysian consumers’ perception toward the extended warranty policy, where we have taken Automobile industrial market as our case study to support our believe that Malaysia which is one of the developing countries in terms of industry, and the automobile market represent from the high marketing level. From that perception, we believe that we can obtain a high investigation records in terms of scale of consumers perception. In this paper we have under taken a survey method as a methodology for conducting the data collection. In particular we have designed questionnaire as our instrumental to assist our investigation in collecting required information from the Malaysian consumers. SPSS software has been used to aid the statistical analysis and analyzed of the data that have been collected using the questionnaire methodology. As a summary, by conducting our survey and gathering the data collection from respondents, we are able to analyze our data and come out with results that can answer our research questions and fulfill our objective.